Hyaluronan synthase 3 deficiency lowers the incidence of ruptures of abdominal aortic aneurysms by reducing monocyte infiltration - Niemann, Viola; Brack, Fedor; Rolauer, Luca; Kaczur, Janet; Petzsch, Patrick; Köhrer, Karl; Quast, Christine; Gerdes, Norbert; Bouvain, Pascal; Voigt, Katharina; Krüger, Martina; Brückner, Alexander; et al. (Frontiers in Immunology, 2025)
IntroductionAbdominal aortic aneurysms and dissections (AAA/AD) are vascular disorders with high mortality due to aortic ruptures. Critical pathomechanisms involve immune cell infiltration and degradation of the vascular extracellular matrix (ECM). Hyaluronan (HA), a major constituent of the ECM synthesized by three HA synthase isoenzymes (HAS1-3), plays a role in both processes. Specifically, HAS3 is crucially involved in inflammatory conditions. Here, we aimed to elucidate the role of HAS3-derived HA in AAA/AD.MethodsMice double-deficient for apolipoprotein E and Has3 (Apoe/Has3-DKO) and littermate controls (Apoe-KO) were studied in a model of angiotensin II (AngII)-induced AAA/AD.ResultsHas3 deficiency improved survival in Apoe/Has3-DKO mice via reducing aortic ruptures. This was associated with decreased monocyte infiltration into the vessel wall. Aortic RNA-Seq analysis indicated disturbed immune cell adhesion and diapedesis. Transfer of Apoe-deficient bone marrow into Apoe/Has3-DKO mice largely normalized the Apoe/Has3-DKO phenotype. While gene expression in endothelial cells (ECs) was not affected, AngII-induced upregulation of proinflammatory cytokines, adhesion receptors and the HA receptor CD44 was attenuated in Apoe/Has3-DKO monocytes. This reduced CD44 cell surface expression in Apoe/Has3-double-deficient monocytes, ultimately inhibiting their in vitro transmigration.DiscussionOur results show that HAS3 plays a key role in AAA/AD formation and suggest the HAS3/CD44 axis as promising therapeutic target to reduce monocyte recruitment and aortic rupture.